2010
DOI: 10.1038/sj.bjc.6605719
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl transferase and breast cancer risk

Abstract: Background:It has been reported that there is an increased risk of cancer in individuals with elevated levels of serum γ-glutamyl transferase (GGT).Methods:In the Guernsey Breast Cancer Cohort Study, GGT was measured in sera from 1803 normal women. Among these women, 251 subsequently developed cancer, of whom 96 developed breast cancer.Results:After adjustment for age at entry, height, weight, age at menarche and first birth with nulliparity, there was a highly significant relationship between elevated GGT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 20 publications
4
24
2
Order By: Relevance
“…A study by Jarari et al [13] reported significantly higher level of serum GGT in breast cancer cases as compared to controls, but the significant hike was observed in the premenopausal group when compared with that of post menopausal similar to our findings. In contrast to our study, increased GGT level was observed in postmenopausal breast cancer patients as compared to premenopausal age group [17,21]. Serum GGT level when compared with patients having different stages of BC, we found proportional increased GGT level from stage I to stage IV and the finding was similar to the study by Chandrakanth et al [16].…”
Section: Resultscontrasting
confidence: 56%
“…A study by Jarari et al [13] reported significantly higher level of serum GGT in breast cancer cases as compared to controls, but the significant hike was observed in the premenopausal group when compared with that of post menopausal similar to our findings. In contrast to our study, increased GGT level was observed in postmenopausal breast cancer patients as compared to premenopausal age group [17,21]. Serum GGT level when compared with patients having different stages of BC, we found proportional increased GGT level from stage I to stage IV and the finding was similar to the study by Chandrakanth et al [16].…”
Section: Resultscontrasting
confidence: 56%
“…In addition, for the fi rst time in a large population-based cohort a significant association between high GGT levels and increased cancer risk in women was shown. Th is is in accordance with recent research on breast cancer risk [35]. In addition, the fi ndings from VHM&PP further suggest GGT to be involved in the progression of premalignant cervical lesions to invasive cancer.…”
Section: Resultssupporting
confidence: 88%
“…In the present investigation, the γ-GT activity was found to be increased in cancerbearing animals. This is well in accordance with the previous finding of Makpol et al, and Fentiman and Allen [54,55].…”
Section: Elumalai Et Alsupporting
confidence: 83%